Śaṅkara and Madhva on the Ī śāvāsya upaniṣad - Archak, K. B. (Krishnamurthy Bheemacharya), 1954- (Archak, 1981)
Comparative study of the Advaita and Dvaita approaches to a Hindu philosophical classic.